The Relationship Between Determinants And Household Consumption Patterns In Lubuk Lintah Village, Padang City - Burhanuddin; Ali Hardana; Wa Ode Irma Sari (CV. Get Press Indonesia, 2025)
This study analyzes the determinants of household consumption patterns in Lubuk Lintah Village, Padang City, focusing on income, family size, education levels, and the prices of essential goods. These factors are critical in shaping how households prioritize expenditures, which ultimately dictates their economic resilience. Using a quantitative approach, the study surveyed 75 purposively selected households, with data analyzed through Pearson correlation and multiple linear regression. The findings indicate that income is the most dominant factor; as earnings increase, households transition from fulfilling basic survival needs to a more balanced allocation across secondary and tertiary goods. The number of family members significantly constrains this balance, as larger households are forced to prioritize high-volume food consumption, leaving little room for non-essential spending. Education acts as a qualitative driver, where higher literacy enables heads of households to manage budgets more rationally and efficiently. Furthermore, fluctuations in the prices of basic necessities create economic pressure that limits consumption flexibility, particularly for lower-income groups. Statistical analysis confirms these relationships, with an value of 0.610, indicating that 61% of the variation in consumption behavior is explained by these variables. In conclusion, consumption patterns in Lubuk Lintah are fundamentally shaped by the interplay of economic capacity and demographic pressure. The study implies that price stabilization policies, income-generating programs, and enhanced financial education are essential to foster more sustainable and balanced household consumption behavior.